Testing of a bipolar solid-state Marx generator for Berlin BESSY II injection kicker system - Redondo, Luis (2021)
This article describes the preliminary results from the new bipolar solid-state Marx generator proposed for Berlin BESSY II injection system, which includes the following pulse specifications: (1) peak voltage of ±8 kV, (2) peak current of 160 A, (3) impedance of 50, (4) frequency ≤10 Hz, (5) width of 350 ns, (6) risetime ≤80 ns, and (7) deviation from “Flat top” ≤ ±1%. The generator is based on SiC metal-oxide-semiconductor field-effect transistors (MOSFETs) in order to allow fast risetime/falltime, where the charging of the main capacitors is from resistive paths. A generator with ten stages, using a dummy load that simulates a kicker magnet, is experimentally tested in order to study the overall performance, and results are presented and discussed.